Formation of a Hollow Core in Dendrimers in Solvents. Issue 15 (7th July 2021) - Markelov, Denis A.; Semisalova, Anna S.; Mazo, Mikhail A.
Abstract: Dendrimers are perfect tree‐like radially symmetric macromolecules with regular branching. Due to their architecture, dendrimers possess a set of unique properties, including high penetrating ability and a large number of functionalizable terminal groups. Practical use of dendrimers as delivery agents or nanoreactors in many cases involves a free space in a dendrimer interior. The question about presence of a hollow core ( a cavity ) inside the dendrimer molecule placed in a solvent attracts interest of researchers since the discovery of dendrimers. This review presents a rigorous discussion on the dendrimer structure in solution. The main objective is to draw attention to the difference in the structure of homopolymer and copolymer dendrimers. Theoretical studies typically consider homopolymer dendrimers (with similar inner and terminal segments), whereas experiments often examine dendrimers with massive terminal groups which chemical structure is different from the structure of the dendrimer inner groups. In the latter case, dendrimer is a copolymer macromolecule, and its conformation can depend on additional factors, such as solvent selectivity, or poor compatibility of terminal and core groups. The influence of these factors can lead to the formation of a region with a lower polymer density inside the dendrimer. Abstract : Dendrimers are perfect tree‐like radially symmetric macromolecules. The question about their hollow core structure attracts a great deal of interest for researchers. In this review, available theoretical and experimental data for homopolymer and copolymer dendrimers are summarized with a conclusion about the possibility of hollow core formation in the latter ones.